Variation of Bone Turnover Markers in Childhood and Adolescence - Yiduo Zhang; Jing Zhang; Xiaocui Huang; Xingnan Yu; Ye Li; Fan Yu; Wenjie Zhou (International Journal of Clinical Practice, 2023)
Objectives. To determine the bone metabolic marker changes from childhood to adolescence and to provide reference values for monitoring bone development in children in Southwest China. Methods. We surveyed 703 participants attending physical examinations from April 2019 and August 2021. Twenty-eight participants were excluded for lack of laboratory tests, and 14 people were excluded for diseases that might affect bone metabolism. A total of 661 children were selected for the study. According to the main developmental periods, the children were divided into preschool, preadolescence, and adolescence groups. Serum bone turnover markers including β-isomerized C-terminal telopeptide of type I collagen (β-CTx), N-terminal midfragment of osteocalcin (N-MID), and procollagen type 1 N-propeptide (P1NP) as well as growth and development indices such as serum calcium (Ca), phosphorus (Pi), alkaline phosphatase (ALP), and vitamin D were measured. The changes in bone metabolism-related markers and the correlations between the indices were analyzed. Results. During the development in boys, the levels of β-CTx and N-MID increased with age from preschool to adolescence, while the levels of P1NP decreased and then increased. In girls, the levels of β-CTx and N-MID plateaued in early adolescence and showed little change in subsequent adolescence, while the levels of P1NP exhibited a downward trend. The correlations between bone metabolism markers and vitamin D were not significant. Conclusions. The levels of bone metabolism markers differed between boys and girls. Reference intervals can be used as essential tools to examine the levels of bone metabolism markers reasonably.